Kajian Teori-Teori Belajar Berdasarkan Sintaks Model Pembelajaran PQDiS-CSR Serta Validasi Model Pembelajaran Model PQDiS-CS: Suatu Penelitian Pendahuluan Pengembangan Model Pembelajaran PQDiS-CSR untuk Meningkatkan Keterampilan Metakognitif - Natalia Rosa Keliat; Herawati Susilo; Utami Sri Hastuti; Ibrohim Ibrohim (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
This research is a mixed study (quantitative-qualitative) that examines learning theories to support the PQDiS-CSR learning model in biology and science learning and tests the validation of the PQDiS-CSR learning model based on survey result from FGD participants. The research subjects are biology and science teachers as well as education experts from Indonesia through FGD (focus group discussion) activities. The results of the study show that there are three learning theories that support this learning model; behaviorism learning theory, constructivism, and information processing systems. he results of the validity test on the development of learning models based on the results of the survey from FGD participants were 4.36 categorized as valid and usable.